ANALYSIS OF WORKLOAD AND NEEDS FOR HEALTH PERSONNEL IN PEUSANGAN SIBLAH KRUENG PUBLIC HEALTH CENTER, A REMOTE AREA OF BIREUEN DISTRICT USING THE WISN METHOD - Machfud Azhari; Aris Winandar (PT. Radja Intercontinental Publishing, 2026)
Peusangan Siblah Krueng Community Health Center is a community health center located in a remote area of Bireuen Regency, Aceh Province, with limited accessibility and a wide coverage area. This study aims to analyze the workload and calculate the need for health workers based on the Workload Indicator of Staffing Need (WISN) method. This study is a quantitative descriptive study with work sampling observations and in-depth interviews. The subjects were all health workers on duty (n=13). Available working time was calculated at 1,883 hours/year. The analysis results indicate a shortage of personnel in the positions of dentist (1 person), nurse (2 people), nutritionist (1 person), and pharmacist/TTK (1 person). The lowest WISN ratio was found in the nursing profession (0.54), indicating a significant workload exceeding the capacity of available personnel. The community health center needs to apply for additional personnel through the Nusantara Sehat mechanism and coordinate with the Bireuen Regency Health Office to meet the personnel standards according to Minister of Health Regulation Number 43 of 2019.